2006
DOI: 10.1120/jacmp.v7i2.2161
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated stereotactic radiotherapy for pediatric patients with retinoblastoma

Abstract: In this report, we discuss the application of a modified Gill‐Thomas‐Cosman (GTC) relocatable head frame to enable fractionated stereotactic radiotherapy (SRT) of infants under anesthesia. This system has been used to treat two infants, ages 12 and 18 months, for bilateral retinoblastoma on a Varian 6/100 linear accelerator. The GTC head frame was used to reproducibly position and treat the orbits of these children to between 2520 cGy and 3960 cGy in 180‐cGy fractions. A standard head and neck tray, with accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Consider the dose to the bony orbit, a common site of secondary malignancies: even optimally applied intensitymodulated radiation therapy will result in 50% of the orbit receiving 50% of the prescribed dose. Higgins et al (2006) used fractionated stereotactic radiation therapy to treat the orbit in children under anesthesia. They found a maximum average deviation to be ± 2 mm.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…Consider the dose to the bony orbit, a common site of secondary malignancies: even optimally applied intensitymodulated radiation therapy will result in 50% of the orbit receiving 50% of the prescribed dose. Higgins et al (2006) used fractionated stereotactic radiation therapy to treat the orbit in children under anesthesia. They found a maximum average deviation to be ± 2 mm.…”
Section: Treatment Methodsmentioning
confidence: 99%
“…In patients treated with focal SRT, median doses to the tumor, optic chiasm, brainstem, ipsilateral optic nerve, globe, lens, orbital bone, and contralateral orbital bone were 41.92, 0.25, 0.07, 9.98, 19.11, 3.74, 6.73 and 2.31 Gy, respectively. In another study comparing SRT with the standard EBRT in 2 cases with bilateral RB, Higgins et al 57 found the normal tissue complication rate reduced from ≥95% to ≤16% with SRT.…”
Section: Novel Techniques Of the External Radiotherapymentioning
confidence: 99%